PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 007 PULAU BIRANDANG - Purnami, Pipit; Syahrilfuddin, Syahrilfuddin; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: the aims of research to improve learning result fourth grade Mathematical student at elementary school 007 Birandang Island by implementing cooperative learning model Make a match. The bacgroun of this research is the low learning result of Mathematics, seen in student value of 23 students. Who are not striking scores of the class was 15 students (65,22%), who reashed the scores of the class was 8 students with an average value. The achievement Standard that school determines 70. The model of research is classroom action research, carried out in two cicles with phases including planning, implementation, observation, and reflection. The technigues of data collection like observation, technique, test and technical documentation. A data collection tod using observation sheet and achievement test. The data analysis technique using teacher and student analysis activity and analysis of student learning result. Inn cycle I, the first meeting of the teacher gained 66,66% with good category, the second meeting of the percentage increased to 75% with good category. In cicle II, the first meeting percentage increased to 83,33% in very well category, at the secont meeting the perscentage icreased to 91,66% with very good category. The average of student learning before the aplication of the model is 58,33 and merease in cycle I to 73,04, and in the second cycle increased to 81,73, the result showed that the aplication of the cooperative model of make a match can improve student learning result of Mathematics.Key Words: Study Result, cooperative learning Model make a match, mathematic